The arhitecture of the human resources in management based on knowledge and the impact on reduncing unemployment - Amalia Venera Todoruţ; George Niculescu; Irina Chirtoc (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2011)
In this working paper I proposed to address/aproach issues of relationship and interdependence of human resources and management based on knowledges. I presented during the paper the new type of human resource management and new challenges which are noted in the current economic conjuncture and their influences on human resource management. We have also shown which is the new type of organizational culture and its impact on management based on knowledge. I focused also on the modalities how influence the management of human resources the management based on knowledge materialized in: the organization employee involvement, strong motivation and retention of employees in the firm based on knowledge, connection of management based on knowledges and the human resource management on the firm strategy, development of employees capacity and the intellectual capital, the creation and maintenance of learning practices widely used in business.